KAJIAN KONSEPTUAL PERILAKU PROSOSIAL DALAM PERSPEKTIF PSIKOLOGI SOSIAL - Islamy, M. Irfan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2015)
Human are homo economicus creatures who always trying to maximize their satisfaction by acting rationally, but they have a desire to see the happiness of others, its called prosocial behavior. Prosocial behavior intended to benefit another